In vitro screening and toxic mechanism exploring of leading components with potential hepatotoxicity of Herba Epimedii extracts. (February 2020) - Zhang, Lin; Xu, An-Long; Yang, Song; Zhao, Bao-Sheng; Wang, Ting
Abstract: Herba Epimedii is a famous Chinese edible herb, and due to its potential hepatotoxic effects, the safety associated with this herb has attracted a great deal of attention. In this study, the components of four types of the Herba Epimedii extracts were identified by HPLC-MS/MS. Among these components, 11 components that were present in all four extracts and could be obtained as reference substances were evaluated for their ability of cytotoxicity in HL-7702 and HepG2 cells, resulting in the identification of icarisid I and sagittatoside A as the most relevant with respect to the toxicity of the extracts. The targeted toxicological effects were further investigated using a series of correlated biological indicators to elucidate potentially hepatotoxic mechanisms. The results showed that the extracts and the selected compounds had varying degrees of influence on the leakage of ALT, AST and LDH; the activity of SOD, GSH and MDA; the increase in intercellular ROS; and the decrease in MMP. Among the tested substances, the ethanol extracts exhibited stronger hepatotoxicity, with icarisid I and sagittatoside A correlating with this toxic effect, and the hepatoxic mechanisms of which may be associated with damaged cell structure, increased oxidative stress and induction of apoptosis. Highlights: 11 components of four types of the Herba Epimedii extracts were quantified. The content of 2 components had notable correlation with the extracts' toxicity. Icarisid I could destroy the cell structure and cause oxidative stress. Sagittatoside A could cause oxidative stress and damage to mitochondria.